The Effect of Red Dragon Fruit (Hylocereus polyrhizus) and Honey on Cholesterol Levels in Menopause - Nara Lintan Mega Puspita; Mayasari Putri Ardela; Putri Erika; Pria Sabilla Putri (Journal of Global Research in Public Health, 2021)
High cholesterol are a serious problem because it can interfere with health even threaten human life. One way to lower high cholesterol levels is by administering red dragon fruit and honey juice. From the initial survey conducted in pustu Datengan Puskesmas Grogol district Kediri the number of menopause with cholesterol levels >200 mg/dl amounted to 42 peaple(10,7%).this study aims to determin the effect of red dragon fruit and honey juice on cholesterol levels in the menopause in pustu Datengan puskesmas Grogol distric Kediri 2021 year. The research design used was pre experimental research with One Group Pre Post Design approach. The population of this is menopause who have cholesterol >200 mg/dl amounted to 16 people. The sampling technique is purposive sampling. The instruments used are Auto Check blood test and observation sheet Results of the research before being given red dregon fruit ang honey juice with an average value of cholesterol levels of 220,94 mg/dl and the results after being given red dragon fruit and honey juice with an average value of cholesterol levels of 199.56 mg/dl. Changes in cholesterollevels before and after treatment were given and mean value of 21.38 mg/dl. On the statistical test result is Wilcoxon test in get ρ value of 0,000 then value ρ value <0,05. This indicates that H0 is rejected and H1 is accepted, meaning that there is influence of red dragon fruit and honey juice to cholesterol levels at menopause in pustu Datengan puskesmas Grogol distric Kediri 2021 year Based on the results of the study is expected menopause can use non pharmacological treatment of red dragon fruit and honey juice to lower high cholesterol levels.